Syndromes associated with children exposure to mycotoxins and health risk assessment to multiple mycotoxins in infant foods - Alvito, Paula (2015)
1. Children health and mycotoxins; 2. Routes of exposure; 3. Syndromes Syndromes associated associated with children children exposure exposure to mycotoxins: to mycotoxins: ingestion and inhalation; 4. Health risk assessment to multiple mycotoxins in infant foods -MYCOMIX project (PTDC/DTP-FTO/0417/2012); 5. Critical role of health professionals